Overlapping and Sequential Copyright, Patent, and Trademark Protections: A Case for Overruling the Per Se Bar - Darden, Loletta (The Columbia Journal of Law & the Arts, 2021)
Should extant or expired copyright or patent designs (such as those featuring Mickey Mouse, Wonder Woman, and the Coca-Cola bottle) be eligible for trademark or trade dress protection? Or, should they enter the public domain upon expiration of the copyright or patent without regard for their source-indicating capacity? The law is in conflict on this question. Early Supreme Court precedent imposed a per se bar precluding trademark or trade dress protection for designs of extant or expired copyrights or patents. Yet, later Supreme Court and regional appellate court cases deviated from that precedent, creating conflicting jurisprudence and promoting marketplace conditions that undermine trademark law’s purpose and policy of maintaining a fair and ordered marketplace. Disallowing trademark protection for nonfunctional source-indicating designs because of their current or past copyright or patent status sets up the possibility for consumer confusion, deception, and fraud in the marketplace. This is precisely the type of marketplace disorder that trademark law is designed to prevent. This Article offers normative justifications for the eligibility of copyright or patent protected designs to receive overlapping and sequential trademark protection, as well as a path for resolving the conflicting jurisprudence. This Article addresses the conflict in overlapping intellectual property protections at the patent/trademark interface and the copyright/trademark interface. At the patent/trademark interface, the per se bar is unnecessary because trademark law’s functionality doctrine properly resolves the concerns with overlapping IP rights, asfunctional designs are categorically ineligible for trademark protection. Unfortunately, the Supreme Court and regional appellate courts use different tests for assessing functionality, yielding inconsistent and conflicting results that are impractical in the new economy. This Article proposes a single functionality test that is more comprehensive than the plethora of existing and conflicting tests currently in use. The proposed test assesses a design’s use in relation to the product and the design’s function in a manner that is less conceptual and more specific to a particular application of the design. At the copyright/trademark interface, the per se bar is also unnecessary for two reasons. First, trademark law’s functionality doctrine resolves the conflict for useful articles. A modified version of the functionality test applied to useful articles precludes trademark-ineligible designs from protection. Second, for character designs and music, it is their specific use that would determine their eligibility for trademark protection. Therefore, the proposed use test would examine that specific use to determine whether the design is being used as a source indicator or as an unlawful attempt to extend copyright protection. The proposed tests at the patent/trademark and the copyright/trademark interfaces provide processes for identifying both functional designs and uses of character designs and music that would be ineligible for trademark protection, further demonstrating that a per se bar is unnecessary. Courts have attempted to ground their reasoning for the per se bar in the copyright and patent law policy that grants the public a right to exploit the subject matter of expired copyrights and patents. This Article posits that trademark law’s public policy for maintaining a fair and ordered marketplace preempts the per se bar’s public policy of a right to copy, rendering the bar inapplicable in the trademark context. There is a presumption running through current jurisprudence that trademark rights must yield to the public’s right to copy, but copyright and patent law are already deemed acceptable incursions on that right. The rules of statutory interpretation, as well as the natural law origin of the right to copy, debunk the presumption that trademark protection must be denied purely because of copyright or patent status. Since there is simply no basis in law or policy for a per se bar of trademark protection, the time has come for Congress or the Court to end the per se bar and resolve the conflict in jurisprudence.